An Overview of Prediction and Control of Air Flow in Acid-Generating Waste Rock Dumps - R Lefebvre; A M. Robertson (The Australasian Institute of Mining and Metallurgy, 2003)
Air movement and associated oxygen transport through waste rock dumps has the potential to significantly enhance the rate of oxidation of pyrite-bearing material. While this is a desired outcome for most heap leach operations, airflow in waste rock storage facilities can result in significant increases in generation and acceleration of acid rock drainage. Hence, a good understanding of internal airflow through waste rock dumps is required to control ARD and minimise any associated liability. The principal mechanisms contributing to airflow and oxygen transport in a waste rock pile include: diffusion; advection due to a thermal gradient (chimney effect) and/or wind pressure gradients; and advection due to barometric pumping. While diffusion is typically limited to a near-surface zone of a few meters depth, advection and barometric pumping have the potential to move air (and oxygen) to much greater depths into the pile. In general, the more permeable the waste rock material, and the greater the height-to-width ratio of the waste rock pile, the greater is the potential for advective air movement. The reactivity of the waste rock material as well as the coarseness (hence air permeability), and the spatial variability of these properties within a pile, have a strong influence on the magnitude of thermally induced advection. In contrast, air movement due to barometric pumping is controlled by the waste rock porosity, changes in ambient air pressure and the heterogeneity of air permeability of the waste rock dump. Results of field monitoring and numerical modelling using TOUGH AMD are presented to illustrate the concepts on air movement in waste rock piles discussed in this paper. During the design and construction phase, airflow can be controlled by judicious placement of reactive waste rock and use of selective placement techniques to control the internal structure of the waste rock facility (eg introduction of horizontal layering, prevention of inclined, high-permeability, channels (æchimneysÆ)). Several closure measures are available to minimise airflow including: placement of a low-permeability cover to reduce air entry; and placement of a non-reactive cover material to isolate reactive material from the zone of active airflow and/or regrading of the waste rock pile to obtain a geometry and internal structure less susceptible to advective airflow.